Association of low potassium diet and folic acid deficiency in patients with CKD - Hassan, Kamal (Ther Clin Risk Manag, 2015)
BACKGROUND: Most of the folic acid sources are rich also in potassium. Patients with chronic kidney disease (CKD) usually receive a low potassium diet. We investigated the possibility of an association between low potassium diet and folic acid deficiency. METHODS: In total, 128 CKD patients participated in this cross-sectional study. Sixty-four patients with CKD grades 1 and 2 were on an unrestricted potassium diet when enrolled in the study, and 64 patients with CKD grades 3 and 4 had received instructions to restrict their intake of potassium at least 6 months before enrollment in the study. Subjects were evaluated for daily intake of folic acid (DI(FA)), daily intake of potassium (DI(K)), and serum folic acid levels (S(FA)). RESULTS: DI(FA) correlated with the estimated glomerular filtration rate, the DI(K), and the S(FA) (P<0.001). S(FA) correlated with the estimated glomerular filtration rate (P<0.001). Mean DI(FA) and mean S(FA) were lower among patients with CKD grades 3 and 4 than among those with CKD grades 1 and 2 (P<0.001). The mean DI(FA) in patients with folic acid deficiency was lower than that in those with S(FA) ≥7.1 nmol/L (P<0.001). There was lower S(FA) and threefold greater frequency of folic acid deficiency among patients with CKD grades 3 and 4 who had received instructions to restrict their intake of potassium than among patients with CKD grades 1 and 2 who were on an unrestricted potassium diet. CONCLUSION: A potassium-restricted diet offered to patients with CKD grades 3 and 4 may be associated with folic acid deficiency. Serum levels of folic acid should be investigated before starting potassium restriction in patients with CKD grades 3 and 4, in order to identify individuals with folic acid deficiency or with marginal serum levels who should receive folic acid replacement therapy.